2006
DOI: 10.1007/s00467-006-0131-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of gentamicin on glomerular and tubular functions in preterm neonates

Abstract: It has been reported that gentamicin causes natriuresis, magnesuria and calciuria in neonates. The aim of this study was to determine the acute effects of trough and peak levels of gentamicin on the values of serum creatinine (SCr), urine albumin/urine creatinine (UA/UCr), fractional excretion of sodium and potassium (FENa, FEK) and urine calcium/urine creatinine (UCa/UCr) in preterm neonates treated with gentamicin for suspected infection. Baseline levels of serum and urine Cr, Na and K and urine albumin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 16 publications
1
23
0
2
Order By: Relevance
“…Therefore, in the absence of glomerular injury, which can cause an increased filtered load that can saturate proximal tubular reabsorption mechanisms resulting in frank proteinuria, the presence of small amounts of albumin in urine is considered indicative of reduced functional (reabsorptive) capacity in the proximal tubules (Russo et al 2007). Microalbuminuria, defined as a urinary albumin loss of 30-300 mg/24 hours, has also been reported in humans treated with cisplatin (Kern et al 2000;Koch Nogueira et al 1998), ifosfamide (Koch Nogueira et al 1998, methotrexate (Koch Nogueira et al 1998), and gentamicin (Tugay et al 2006). However, microalbuminuria may also occur in the setting of vigorous exercise, urinary tract infection, and dehydration .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the absence of glomerular injury, which can cause an increased filtered load that can saturate proximal tubular reabsorption mechanisms resulting in frank proteinuria, the presence of small amounts of albumin in urine is considered indicative of reduced functional (reabsorptive) capacity in the proximal tubules (Russo et al 2007). Microalbuminuria, defined as a urinary albumin loss of 30-300 mg/24 hours, has also been reported in humans treated with cisplatin (Kern et al 2000;Koch Nogueira et al 1998), ifosfamide (Koch Nogueira et al 1998, methotrexate (Koch Nogueira et al 1998), and gentamicin (Tugay et al 2006). However, microalbuminuria may also occur in the setting of vigorous exercise, urinary tract infection, and dehydration .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, microalbuminuria may prove to be a useful marker of AKI and concomitant proximal tubular cell damage. Microalbuminuria has previously been reported with shortterm and long-term administration of nephrotoxic chemotherapeutics (Koch Nogueira et al, 1998;Kern et al, 2000) and antibiotics (Tugay et al, 2006). Microalbuminuria, however, may also occur in the setting of vigorous exercise, hematuria, urinary tract infection, dehydration, fever, and poor glycemic control.…”
Section: Microalbuminuriamentioning
confidence: 95%
“…Tugay et al showed gentamicin administration in preterm newborns increase urine calcium excretion from day 3 onwards. 15 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some studies in newborns and animals have shown that gentamicin increases urinary calcium excretion. [11][12][13][14][15] Injection every 36-48 hours is a new recommendation for intravenous gentamicin treatment in newborns. 3 Following this new recommendation, there have been no further studies on the effects of extended gentamicin dosage on urinary calcium excretion in newborns.…”
Section: G Entamicin Is a Common First-line Antibiotic Therapy For Inmentioning
confidence: 99%